Age of Digital Marketing Communication and its Influence on Consumer Buying Behavior-With Special Reference to Rajasthan (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The Internet is a major area of digital marketing because it is a comprehensive communication channel available to all types of businesses. In fact, this can give credence to the fact that digital marketing is an important part of e-commerce. This is because e-commerce cannot exist without internet marketing. Anyone involved in e-commerce must continually implement strategies to attract customers, which is one of the most important characteristics of online success. Therefore, e-commerce and digital marketing have always been closely related because marketing is essential to increase sales. As per the reports of TRAI (2017) it is clear that maximum users of internet are between the age of 16 to 35. In this present study the researcher has considered the students of engineering colleges of Jaipur as respondents and conducted a survey. The results will present the basis of inclination and the variation in inclination towards the use of internet for seeking information and related aspects. This study is based on primary data.